Kain Tenun Songket Melayu Batu Bara: Sejarah, Motif dan Fungsinya - Wati, Dedek Ambar; Irwansyah, Irwansyah; Devianty, Rina (Mahesa Research Center (PT. Mahesa Global Publishing), 2022)
This article discusses the history, motifs, and functions of the Batu Bara Malay songket woven fabric. Coal Malay songket woven cloth is a traditional cloth that is the cultural heritage of the Batu Bara community. Historically, the Coal Malay songket woven fabric has existed since 1823, while the shapes and motifs used in the Coal Malay songket woven fabric are usually in the form of plants and nature. The Batu Bara Malay songket woven cloth serves as a symbol and identity for the Malay community in Batu Bara. The method used in this research is descriptive qualitative with a historical approach. The results showed that the use of the Batu Bara Malay songket woven fabric had existed since the reign of the Batu Bara Sultanate, at that time the Batu Bara community had begun to recognize the materials and threads used to make songket woven fabrics. Since its inception until now, the Malay Coal songket woven cloth has been used for various traditional activities. Almost every traditional Malay ceremony and activity always uses songket. The motifs and colors used in the Batu Bara Malay songket used to reflect the strata or social status of the person who wore it.